Defect-induced magnetism in two-dimensional NbSe2. (January 2017) - Manchanda, P.; Skomski, R.
Abstract: The energetics and magnetism of perfect and vacancy-containing two-dimensional NbSe2 monolayers is investigated by first-principle calculations. It has been found the single Se vacancy has the lowest formation energy. Perfect NbSe2 monolayers, as well as monolayers containing single-selenium and double-selenium vacancies, are nonmagnetic metallic. However, Nb vacancies create a magnetic moment of 1.5 μ B per vacancy. The moment is highly localized, confined nearly exclusively on the Se atoms adjacent to the vacancy, and mainly originates from the Se 4 p electrons. The moment distribution indicates strongly anisotropic exchange bonds between vacancy moments. Highlights: The energetics and magnetism of defect containing NbSe2 monolayers are investigated by first-principle calculations. Single Se vacancy has the lowest formation energy but it is nonmagnetic metallic. Nb vacancies create a magnetic moment of 1.5 μ B per missing Nb atom caused by Se 4 p electrons.